Results of coronary bypass surgery performed in the early stages of non-ST segment elevation acute coronary syndrome - Yu. V. Neverova; R. S. Tarasov; S. V. Ivanov; A. B. Nishonov; L. S. Barbarash (Российский кардиологический журнал, 2019)
Aim. The question of choosing the optimal revascularization strategy for patients with acute coronary syndrome without ST-segment elevation (NSTE-ACS) and multivessel coronary disease (MVCD) remains open. The aim of the work was to assess the results of revascularization by the method of coronary artery bypass grafting (CABG), performed in the early stages of NSTE-ACS.Material and methods. During the 2016-2018 period we included 87 consecutive patients with NSTE-ACS and MVCD, who underwent CABG. Depending on the timing of revascularization, the patients were divided into 4 groups: the first 24 hours, 24-72 hours, 72 hours — 7 days, more than 7 days — hospital period. Endpoints of the study were such adverse cardiovascular events as death, myocardial infarction (MI), acute cerebrovascular accident/transient ischemic attack, repeated revascularization, bleeding on the BARC scale (Bleeding Academic Research Consortium). Endpoints were evaluated in the hospital period.Results. Patients of the studied sample were characterized by severe clinical and angiographic status. The mean value of SYNTAX Score was 36 (33; 38) points, GRACE — 136 (123; 144) points. Hemodynamically significant lesion of the left coronary artery was detected in 40% of patients. MI was recorded in 44% of patients, 48% of patients had diabetes. In 8% of cases, patients underwentrevascularization within 24 hours from the time of admission to the clinic, in 9% — in the time interval from 24 to 72 hours, in the remaining cases — during the hospital period. Ninety four percent of the operations were performed under cardiopulmonary bypass. The SYNTAX Score value after CABG in the group was not more 5 (3; 7) points. The average volume of blood loss was 550±150 ml. The total number of deaths was 4,6%.Conclusion. The high need for CABG, as a reasonable strategy of revascularization for patients with NSTE-ACS and MVCD, and satisfactory results of the surgery demonstrate the need for accessibility of CABG in 24/7 mode, as a percutaneous coronary intervention.